1993
DOI: 10.1177/095632029300400406
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV Infection by Caffeoylquinic Acid Derivatives

Abstract: The caffeoylquinic acids 3,4,5-tri-O-caffeoylquinic acid (1) and 4,5-di-O-caffeoylquinic acid (2), as well as caffeic acid (4) and synapoic acid (5) were isolated from the plant Securidaka longipedunculata (polygalaceae). 1 exhibited a greater selective inhibition of HIV replication than 2 which had an anti-HIV activity similar to that of 3,4,5-tri-O-galloylquinic acid (3), isolated from Guiera senegalensis (combretaceae); 4 and 5 were ineffective and the structurally related compound rosmarinic acid (6) had o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 15 publications
4
99
0
1
Order By: Relevance
“…This research opens the possibility for the use of these substances as a food additive and a remedy for the prevention and treatment of diabetes and obesity (Okudaira et al, 2005). Isochlorogenic acids a, b and c (24-26) are also found in other species of Ipomoea, such as I. batatas and I. pes-caprae and exhibited colagenase inhibitory and were almost nocytotoxic (Teramachi et al, 2005), beyond to showed radical scavenging activities (Islam et al, 2003) and inhibition of HIV infection (Mahmood et al, 1993;Islam et al, 2002a). Isochlorogenic acids a (24) presents still antifungal activity (Stange et al, 2001) and significant anti-spasmodic activity (Trute et al, 1997).…”
Section: Stansmentioning
confidence: 99%
See 1 more Smart Citation
“…This research opens the possibility for the use of these substances as a food additive and a remedy for the prevention and treatment of diabetes and obesity (Okudaira et al, 2005). Isochlorogenic acids a, b and c (24-26) are also found in other species of Ipomoea, such as I. batatas and I. pes-caprae and exhibited colagenase inhibitory and were almost nocytotoxic (Teramachi et al, 2005), beyond to showed radical scavenging activities (Islam et al, 2003) and inhibition of HIV infection (Mahmood et al, 1993;Islam et al, 2002a). Isochlorogenic acids a (24) presents still antifungal activity (Stange et al, 2001) and significant anti-spasmodic activity (Trute et al, 1997).…”
Section: Stansmentioning
confidence: 99%
“…Chlorogenic acid (23) and 3,4,5-tri-O-caffeoylquinic acid (27) were also found in I. batatas. These compounds are also inhibitors of HIV replication (Mahmood et al, 1993) and present hypoglycaemic (Okudaira et al, 2005), radical scavenging (Islam et al, 2003) and antimutagenic (Yoshimoto et al, 2002) activities. Chlorogenic acids were not detected in the root.…”
Section: Stansmentioning
confidence: 99%
“…4,17,18) The koji extract also hydrolyzed the crude polyphenolic extract of sweetpotato, burdock, and mugwort leaves to CA (Fig. 3).…”
Section: -7)mentioning
confidence: 99%
“…Sweet potatoes have been reported to have a range of beneficial functionalities due to high contents of chlorogenic acids. The chlorogenic acids extracted from sweet potato were found to inhibit the growth of human colon, leukemia, and stomach cancer cells, to ameliorate diabetes in humans, and to inhibit growth of viruses and fungi [3][4][5][6]. Caffeoyl quinic acids isolated from Japanese sweet potato leaves exhibited antimutagenic activities J ournal of Food Chemistry & Nanotechnology Impact of solvent system on the chlorogenic acids extraction from sweet potatoes Sweet potatoes were first sliced into thin pieces, then freeze-dried and ground to make fine powder to pass through a 150 mm sieve.…”
Section: Introductionmentioning
confidence: 99%